Factors that Influence the Recognition, Reporting, and Resolution of Incidents Related to Medical Devices and an Investigation of the Continuous Quality Improvement Data Automatically Reported by Wireless Smart Infusion Pumps - Polisena, Julie (Université d'Ottawa / University of Ottawa, 2015)
Medical devices are used to diagnose, treat, or prevent a disease or abnormal physical condition without any chemical action in the body. They can also result in unintended incidents and other errors. This thesis was divided into three chapters: i) a systematic review on the recognition, reporting and resolution of incidents related to medical devices and other health technologies; ii) telephone interviews with physicians and registered nurses (RNs) to solicit information on the resolution, reporting and resolution of medical device-related incidents based on their professional experience; and iii) a case study to review the continuous quality improvement (CQI) data retrieved from the wireless smart infusion pump system at The Ottawa Hospital (TOH) and to propose a CQI data analysis process. The systematic review included 30 studies on factors that influence the recognition, reporting and resolution of incidents in hospitals and interventions to improve patient safety. Central themes that emerged for incident reporting were personal attitudes, awareness and perception of incident reporting systems, organizational culture, and feedback to healthcare professionals. In our telephone interviews, physicians and RNs attributed incident recognition to devices not operating based on the manufacturer’s instructions, and to the hospital staff’s knowledge of and professional experience with the use of the medical device, and clinical manifestations of patients. Suggestions to improve medical device safety surveillance centered on education and training to ensure that the staff is able to use the medical device properly and know what would be considered an error, and how to report these errors. The results of the systematic review and interviews helped to inform the design of a medical device surveillance framework in a hospital setting. Our case study assessed the Dose Error Reduction Software compliance and frequency of soft and hard limit alerts with wireless smart infusion pump systems over a one year period. A CQI data analysis process to monitor the performance of wireless smart infusion pumps is proposed. The findings of this doctoral thesis can contribute to the development of a medical device surveillance system that would help to improve health care delivery and patient safety in a health care institution.
Keywords: medical devices; health technology; post-market surveillance; incidents; medication errors; infusion pumps; continuous quality improvement; patient safety; hospital